2024
DOI: 10.1021/acs.energyfuels.3c05171
|View full text |Cite
|
Sign up to set email alerts
|

Pore-Scale Investigation into the Effects of Fluid Perturbation During Hydrate Formation

Xu Rui,
Yu Deng,
Jing-Chun Feng
et al.

Abstract: In order to increase the gas production efficiency during methane hydrate exploitation, the research focus should be nowadays on the methane hydrate formation and decomposition mechanisms. As methane hydrate reformation and the hydrate heterogeneity in the pores of sediments show great influence on gas production during hydrate decomposition, new insights need to be supplemented to reveal the mechanism of the hydrate phase transition. In this work, a new microfluidic chip 'simple straight pipe chip' was design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…In recent years, there has been significant advancement and enrichment in visualization techniques, , with the utilization of X-ray or optical microscopy, emerging as a prevailing research trend for studying the formation dynamics of hydrates. Rui et al observed that under gas-filled conditions, as the water migration rate increases, the hydraulic stability transitions from grain-coating hydrate to grain-filling hydrate and finally to load-bearing hydrate. Yang et al conducted a numerical simulation of hydrate dissociation by depressurization and revised the kinetic model but lacked analysis on the physical properties of hydrates.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, there has been significant advancement and enrichment in visualization techniques, , with the utilization of X-ray or optical microscopy, emerging as a prevailing research trend for studying the formation dynamics of hydrates. Rui et al observed that under gas-filled conditions, as the water migration rate increases, the hydraulic stability transitions from grain-coating hydrate to grain-filling hydrate and finally to load-bearing hydrate. Yang et al conducted a numerical simulation of hydrate dissociation by depressurization and revised the kinetic model but lacked analysis on the physical properties of hydrates.…”
Section: Introductionmentioning
confidence: 99%